2022
DOI: 10.25105/jat.v9i2.14005
|View full text |Cite
|
Sign up to set email alerts
|

The Moderating Role of Environmental Management Accounting on Firm Value

Abstract: In this study, the authors are interested in examining how the influence of Sustainability Performance, External Assurance and Green Innovation on Firm Value with Environmental Management Accounting as a Moderating Variable. This study uses a population of all companies listed on the Indonesia Stock Exchange from 2015 to 2020 which found 138 samples, according to the criteria needed in this study there were only 23 companies that were sampled for 2015 to 2020. This study used regression analysis. multiple line… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 41 publications
0
2
0
1
Order By: Relevance
“…Few recent studies have investigated the mediating and moderating roles of EMA in the relationships between other variables; for instance, ref. [26] provides strong evidence of the moderating role of environmental management accounting, as it strengthens the positive influence of sustainability performance and green innovation on firm value. Additionally, the findings of [12] revealed that EMA, measured in terms of eco-efficiency, has a positive impact on corporate sustainability, as they indicated that the high eco-efficiency performance of businesses reflects minimal energy use.…”
Section: Interaction Between Eco-efficiency and Emamentioning
confidence: 86%
“…Few recent studies have investigated the mediating and moderating roles of EMA in the relationships between other variables; for instance, ref. [26] provides strong evidence of the moderating role of environmental management accounting, as it strengthens the positive influence of sustainability performance and green innovation on firm value. Additionally, the findings of [12] revealed that EMA, measured in terms of eco-efficiency, has a positive impact on corporate sustainability, as they indicated that the high eco-efficiency performance of businesses reflects minimal energy use.…”
Section: Interaction Between Eco-efficiency and Emamentioning
confidence: 86%
“…Berlandaskan penelitian sebelumnya, diidentifikasi beberapa faktor yang dapat mempengaruhi harga saham, seperti: leverage, family control, ukuran perusahaan, pertumbuhan perusahaan (Holly et al, 2022); environmental management accounting (Wicaksono & Tarisa, 2022); family business (Anggadwita et al, 2020); struktur modal, family control, profitabilitas, pertumbuhan perusahaan (Sholaihah & Laily, 2020); kebijakan dividen, keputusan investasi, keputusan pendanaan (Piristina & Khairunnisa, 2019); dividend policy, investment decisions, profitabilitas, financial performance (Chandra et al, 2019); dan manajemen asset, kebijakan hutang, profitabilitas (Putri et al, 2018). Berdasarkan hasil penelitian yang tidak konsisten, yang diyakini dapat mempengaruhi nilai perusahaan akan digunakan sebagai variabel dependen untuk penelitian adalah Family control, Environmental Management Accounting (EMA) dan Profitabilitas.…”
Section: Pendahuluanunclassified
“…Referring to research conducted by Yuniarti et al (2022) which suggests using different measurements of green innovation, this research applies measurements carried out by Agustia et al (2019), Damas and Tarisa (2022) using the Green Innovation Checklist The index and object carried out are by using a manufacturing company. This is because according to environmental problems it is mainly caused by manufacturing companies and because manufacturing has a big impact on sustainable and environmentally friendly economic growth (Lin, H, Zeng 2017).…”
Section: Introductionmentioning
confidence: 99%